2022
DOI: 10.1155/2022/7576132
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anticholinesterase Properties of the Aqueous Extract of Balanites aegyptiaca L. Delile Fruit Pulp on Monosodium Glutamate-Induced Excitotoxicity in Swiss Mice

Abstract: Balanites aegyptiaca L. Delile (B. aegyptiaca) is used in traditional medicine for the treatment of memory impairment. This work aims to evaluate the antioxidant and anticholinesterase potential of BA fruit pulp extract on excitotoxicity induced by monosodium glutamate (MSG). MSG was administered 30 minutes after treatment with B. aegyptiaca aqueous fruit pulp extract (50, 125, 250, and 500 mg/kg) and vitamin C (100 mg/kg) for 30 days. The negative control group received only MSG, while the control group was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…However, the data from these studies vary due to differences in diet. Therefore, monosodium glutamate (MSG) is often used to induce obesity [ 12 , 13 ], including in our previous studies [ 14 , 15 , 16 ]. In our previous studies on mice with MSG-induced obesity, we found that lipid droplets accumulated in the hepatocytes in the obese mice [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the data from these studies vary due to differences in diet. Therefore, monosodium glutamate (MSG) is often used to induce obesity [ 12 , 13 ], including in our previous studies [ 14 , 15 , 16 ]. In our previous studies on mice with MSG-induced obesity, we found that lipid droplets accumulated in the hepatocytes in the obese mice [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to clinical studies, animal models have been used for basic research on chronic obesity [3][4][5]. For instance, the administration of monosodium glutamate (MSG) immediately after birth can be used to develop animal models of chronic obesity [6][7][8]. Since the hypothalamus is still immature immediately after birth, administered MSG crosses the blood-brain barrier (BBB) and flows into the hypothalamus, destroying nerve cells associated with satiety and the bioenergetic control center [9,10].…”
Section: Introductionmentioning
confidence: 99%